Effect of Consumption of Camu Camu Fruit Extract on Sperm DNA Integrity in Mice Pretreated with a Single Dose of Cyclophosphamide: Efecto del Consumo del Extracto del Fruto “Camu Camu” en la Integridad del ADN Espermático de Ratones Pretratados con Dosis Única de Ciclofosfamida | “Camu Camu”果实提取物对单次环磷酰胺预处理小鼠精子DNA完整性的影响 - Pino Gaviño, Jose Luis (2024)
Introduction: Myrciaria dubia known as “camu camu” is a fruit that grows in the Amazon and its main characteristic is its high content of vitamin C. Ascorbic acid has a protective role in spermatogenesis as it is a compound that has excellent reducing action. The purpose of this research was to evaluate in vivo the cytoprotective capacity of the aqueous extract of the fruit of Myrciaria dubia (Kunth) McVaugh “camu-camu” against the mutagenic damage produced by the antineoplastic drug cyclophosphamide (CP) on the male germ line. Methodology: Mice (n= 60) were divided into five treatment groups: T1= negative control (without treatment); T2 ingested the aqueous extract (10mgkg-1), T3 ingested the aqueous extract (50mgkg-1), T4 ingested the aqueous extract (100mgkg-1); T5 is the positive control. All of them were injected with a single dose of CP (50 mgkg-1) intraperitoneally. Treatment with camu-camu continued for 45 days, then the mice were euthanized to determine sperm quality and the frequency of DNA damage using the Index protocol. Sperm DNA fragmentation – Halomax protocol. Results: The effect of camu-camu extract was observed in all trials (p< 0.05) compared to the negative control. Group T4, which was administered the highest concentration of the aqueous extract of the fruit, evidenced the cytoprotective effect of camu-camu (p< 0.05). Conclusion: The damaging effect on DNA due to the oxidative action of CP is inhibited by the aqueous extract of the “camu camu” fruit.